2016
DOI: 10.15516/cje.v18i4.1774
|View full text |Cite
|
Sign up to set email alerts
|

Social Entrepreneurship Education and Its Association with Perceived Desirability and Feasibility of Social Entrepreneurship among Business Students / Obrazovanje za socijalno poduzetništvo i njegova povezanost s percepcijom poželjnosti i izvodljivosti so

Abstract: The purpose of this study was to examine the association between social entrepreneurship education and experience in prosocial behaviour on the one hand and the perceived desirability and feasibility of social entrepreneurship among business students on the other. A sample consisting of business students was selected bearing in mind the possible implications of this study on business education curricula. The sample included 512 soon-to-graduate business students from five countries: Austria, Bosnia and Herzego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
19

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 26 publications
3
15
0
19
Order By: Relevance
“…The traditional way in which universities may affect the SEI of students is through the offering of social entrepreneurship education programs. The impact of social entrepreneurship education programs on the precursors of the SEI of students has been the subject of several studies in the past (Adelekan et al, 2018;Hockerts, 2017;Kedmenec et al, 2017;Kwong et al, 2012;Piperopoulos & Dimov, 2015;Smith & Woodworth, 2012;Tshikovhi & Shambare, 2015). The investigation of other aspects of the university's ESS such as business incubation and spin-offs (Chiesa & Piccaluga, 2000;Hughes, Ireland, & Morgan, 2007;Markuerkiaga, Caiazza, Igartua, & Errasti, 2016;Mian, 1996Mian, , 1997, technology transfer mechanisms (Bray & Lee, 2000;Etzkowitz, 2003;Poole & Robertson, 2003), university venture funds (Lerner, 2004) and mentoring and networking (Nielsen & Lassen, 2012) are less common in the literature to date.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The traditional way in which universities may affect the SEI of students is through the offering of social entrepreneurship education programs. The impact of social entrepreneurship education programs on the precursors of the SEI of students has been the subject of several studies in the past (Adelekan et al, 2018;Hockerts, 2017;Kedmenec et al, 2017;Kwong et al, 2012;Piperopoulos & Dimov, 2015;Smith & Woodworth, 2012;Tshikovhi & Shambare, 2015). The investigation of other aspects of the university's ESS such as business incubation and spin-offs (Chiesa & Piccaluga, 2000;Hughes, Ireland, & Morgan, 2007;Markuerkiaga, Caiazza, Igartua, & Errasti, 2016;Mian, 1996Mian, , 1997, technology transfer mechanisms (Bray & Lee, 2000;Etzkowitz, 2003;Poole & Robertson, 2003), university venture funds (Lerner, 2004) and mentoring and networking (Nielsen & Lassen, 2012) are less common in the literature to date.…”
Section: Discussionmentioning
confidence: 99%
“…This process revealed that no previous researcher has considered the SEI of students as influenced by the university's ESS per se. Some researchers who studied the influence of the university on the SEI of students did so in relation to the effect of social entrepreneurship education (Adelekan, Williamson, & Atiku, 2018;Kedmenec, Rebernik, & Tominc, 2017;Kwong, Thompson, & Cheung, 2012;Piperopoulos & Dimov, 2015;Smith & Woodworth, 2012;Tshikovhi & Shambare, 2015). Thus, the authors modified the inclusion criteria to contain articles that deal with the SEI of students in more general terms.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations